The Influence of Work Discipline and Supervision on Employee Performance with Communication as an Intervening Variable at Head Office PT. Jasindo Insurance - Guntur Nasution; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2023)
One of the most important parts of human resources in a company is employees. Employees are the main driver of the performance, smoothness and survival of a company, so to achieve the desired goals it is important for companies to maintain and improve the performance of their employees. This research aims to determine the effect of work discipline and supervision on employee performance with communication as an intervening variable with associative quantitative research, this research was conducted at the Head Office of PT. Jasindo Insurance. The population of this study was 80 employees and the sample used was 80 employees (saturated sample). Data was collected by distributing questionnaires and the research model used was path analysis. The measuring tool used for this research was Smart PLS version 3.3.3. The results of this research are as follows: Work Discipline has a positive and insignificant effect on Employee Performance. Work Discipline has a positive and significant effect on Communication. Communication has a positive and significant effect on employee performance. Supervision has a positive and significant effect on employee performance. Supervision has a positive and insignificant effect on communication. Work Discipline has a positive and insignificant effect on Employee Performance through Communication. Supervision has a positive and insignificant effect on employee performance through communication.